The Suppression of Wound Healing Response with Sirolimus and Sunitinib Following Experimental Trabeculectomy in a Rabbit Model - Eren, Kenan; Turgut, Burak; Akin, Mehmet Mustafa; Demir, Tamer (Taylor & Francis Inc, 2016)
Purpose: To investigate the effects of sirolimus and sunitinib on wound healing in experimental glaucoma filtering surgery (GFS). Material and Methods: Thirty-five male New Zealand pigmented rabbits were randomly assigned to five groups, each including seven rabbits: The rabbits in the control group were not operated on and did not receive any treatment. The rabbits in the sham group underwent trabeculectomy and had one drop of saline instilled four times a day for 14 days. The rabbits in the mitomycin-C (MMC) group underwent trabeculectomy, and a sponge soaked in 0.4mg/mL MMC was applied intraoperatively to the scleral surgical site for three minutes. The rabbits in the sirolimus group underwent trabeculectomy and 30 ng/mL sirolimus-soaked sponge was applied intraoperatively to the scleral surgical site for three minutes. Sunitinib 0.5mg/mL four drops in a day were applied in the sunitinib group for 14 days after surgery. On day 14 of the experiment, eyes were enucleated and histologically and immunohistochemically analyzed. Statistical analyses of the study were performed with Kruskal-Wallis variance analysis and Mann-Whitney U test. Results: The mean fibroblast and MNC numbers and the mean immunostaining intensities of transforming growth factor-beta (TGF-beta), fibroblast growth factor-beta (FGF-beta) and platelet derived growth factor (PDGF) in the MMC, sirolimus and sunitinib groups were statistically significantly lower than those of the sham group (p<0.01). The mean fibroblast and MNC numbers and the mean immunostaining intensities of TGF-beta, FGF-beta and PDGF in the MMC, sirolimus and sunitinib groups were similar (p>0.05). Conclusions: Our study suggests that the applications of sirolimus and sunitinib effectively suppress the subconjunctival scarring after experimental GFS.
Keywords: Experimental; glaucoma; mitomycin-C; sirolimus; sunitinib; trabeculectomy